Impact of On-Farm Demonstrations on Technology Adoption, Yield, and Profitability Among Small Farmers of Wheat in Pakistan—An Experimental Study - Nadia Hussain; Keshav Lall Maharjan (Agriculture)
Do the intensive demonstrations result in consistent technology adoption and yield enhancement? While extension methods show significant immediate effects of an intervention, their impact may fade over time. In a government-led natural experiment in Pakistan, a long-lasting adoption of certified seeds, fertilizers, and pesticides/herbicides in post-treatment years were observed by employing difference–indifferences with a fixed effect method on panel data. The intervention increased the technology adoption in terms of certified seeds by 34%, fertilizers by 15 kg/ha, and pesticides/herbicides by 0.22 L/ha among adopters for four years. Similarly, the wheat yield increased by 0.41 tons per hectare, and profit increased by 12% among the treatment group compared to the control group. In view of these findings, this study suggests continuing this supervised method of extension to other crops in Pakistan.